2018
DOI: 10.1037/edu0000237
|View full text |Cite
|
Sign up to set email alerts
|

Teaching writing in primary education: Classroom practice, time, teachers’ beliefs and skills.

Abstract: The aim of this study was to provide insight into the current practice of writing instruction in Dutch primary education, as a stepping stone for designing and implementing sustainable innovations that could satisfy both practitioners and policymakers. We investigated the extent to which three domain-specific approachescommunicative writing, process writing, and writing strategy instruction-and general features of high-quality instruction were implemented in writing lessons in the upper grades of primary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 54 publications
5
78
0
14
Order By: Relevance
“…Furthermore, in each of the three interventions students' writing performance was measured with just one writing task at pretest and posttest. This is problematic, because previous studies have shown that students' writing scores tend to differ strongly across tasks (Schoonen, 2012;Rietdijk et al, 2018). In future studies, more writing tasks are needed to estimate students´ writing skill more precisely.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, in each of the three interventions students' writing performance was measured with just one writing task at pretest and posttest. This is problematic, because previous studies have shown that students' writing scores tend to differ strongly across tasks (Schoonen, 2012;Rietdijk et al, 2018). In future studies, more writing tasks are needed to estimate students´ writing skill more precisely.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…For our history teachers, who taught writing for the first time, direct and explicit writing strategy instruction might have been a step too far. After all, writing strategy instruction is still relatively uncommon in Dutch writing education (Mottart et al, 2009;Rietdijk, van Weijen, Janssen, van den Bergh, & Rijlaarsdam, 2018), and difficult to implement in a normal classroom practice (De La Paz, 2007). A next step for these teachers might be to include explicit process related writing instruction in their teaching.…”
Section: Effects On Knowledge Of Writingmentioning
confidence: 99%
“…Writing strategy instruction, for instance, is rather uncommon in Dutch primary education, as shown by Rietdijk, Van Weijen, Janssen, Van den Bergh, & Rijlaarsdam (2018) in an analysis of teacher interviews and classroom observations. However, recently two writing programs based on strategy instruction have been developed and tested in Dutch primary schools: Tekster (Bouwer & Koster, 2016) and Better Writing (Rietdijk, Janssen, Van Weijen, Van den Bergh, & Rijlaarsdam, 2017).…”
Section: Meta-analyses: Conclusionmentioning
confidence: 99%
“…We examined the instruments used in 14 different studies. We started by examining the instruments used in the most recent Dutch periodic writing assessments (Krom et al, 2004;Kuhlemeier et al, 2013) and instruments that were used in recent Dutch and Flemish research into writing in elementary education (De Smedt et al, 2016;Franssen & Aarnoutse, 2003;Henkens, 2010;Rietdijk et al, 2018). We supplemented this group of studies with instruments from studies used as a theoretical basis for the Writing Framework (Kyriakides et al, 2009;Van de Grift, 2007) and with questionnaires developed by Steve Graham's research group (Cutler & Graham, 2008;Gilbert & Graham, 2010;Graham et al, 2002;.…”
Section: Instruments For Assessing Writing Instructionmentioning
confidence: 99%
“…The insights may benefit writing education in Dutch primary schools, which may be generally characterized as a process-oriented approach from a broad perspective on writing (Hoogeveen, 2018;Van Gelderen, 2010), although research in the primary school classrooms, among which periodic inquiry from the Dutch Inspectorate for Education, has shown that writing education is predominantly product-oriented (Pullens, 2012;Bonset & Hoogeveen, 2015;Henkens, 2012). A recent inquiry by Rietdijk et al (2018) demonstrated however that teachers mainly support a view of writing as a way to create a text involving personal thinking (a transactional view on writing; White & Bruning, 2005), rather than as a way to provide readers with information from authoritative sources (regarding 'correct writing' as the main focus of writing instruction). Observing students while writing together and taking a more process oriented approach to the joint construction of texts, including attention to the role of creative interthinking (Mercer & Littleton, 2010), may be important conditions for optimizing writing practices in the primary school classrooms.…”
Section: Developmental Aspects Of Writing Proficiency and Pragmatic Smentioning
confidence: 99%